LED spotlight for improving clothing display effect in clothing shop - YUAN YUQIN (2022)
The utility model relates to the technical field of commercial lighting, and discloses an LED spotlight for improving the clothing display effect in a clothing shop, which comprises a box body, a motor is fixedly mounted on the left side of the inner cavity of the box body, a threaded rod is fixedly mounted at the output end of the motor through a speed reducer, and a movable block is mounted on the outer surface of the threaded rod in a threaded manner; according to the LED spotlight for improving the clothing display effect in the clothing shop, the motor is started to be matched with the threaded rod, the movable block, the supporting rod and the connecting rod to drive the spotlight body to horizontally move left and right, so that the LED spotlight is convenient to use, and the clothing display effect is improved. And then the electric telescopic rod is started to be matched with the buckle and the connecting rod to drive the lamp to longitudinally swing, the purpose of adjusting the transverse irradiati